Tapinarof Cream 1% Once Daily for the Treatment of Plaque Psoriasis: Case Photography of Clinical Outcomes from Three Phase 3 Trials - Seemal R. Desai; Linda Stein Gold; Michael C. Cameron; Alexandra Golant; G. Michael Lewitt; Matthew J. Bruno; George Martin; Philip M. Brown; David S. Rubenstein; Victoria Butners; Anna M. Tallman (Adis, Springer Healthcare, 2023)
Abstract Tapinarof cream 1% (VTAMA®; Dermavant Sciences, Inc.) is a non-steroidal, topical, aryl hydrocarbon receptor agonist approved by the US Food and Drug Administration (FDA) to treat plaque psoriasis in adults and under investigation for the treatment of psoriasis in children down to 2 years of age, and for atopic dermatitis in adults and children down to 2 years of age. The PSOARING phase 3 clinical trial program evaluated tapinarof cream 1% once daily (QD) in adults with mild to severe plaque psoriasis for up to 52 weeks (NCT03956355, NCT03983980, NCT04053387). Here we present case photography documenting outcomes in the PSOARING trials. Cases illustrate various outcomes across different body areas, including responses meeting the formal FDA-mandated regulatory endpoint of a Physician Global Assessment (PGA) score of 0 (clear) or 1 (almost clear) and a decrease of at least 2 points from baseline at week 12, meaningful clinical improvement not meeting this formal endpoint, patient-reported outcomes, and pre-specified adverse events of special interest (AESIs). Tapinarof cream 1% QD demonstrated rapid and highly statistically significant efficacy, with improvements in disease activity and quality of life. In addition, a high rate (40.9%; n = 312/763) of complete disease clearance (PGA = 0) was achieved, and improvements exceeding National Psoriasis Foundation treatment goals were demonstrated. After first achieving complete disease clearance (PGA = 0), patients treated with tapinarof experienced an approximately 4-month remittive effect off therapy. Incidence and severity of folliculitis and contact dermatitis AESIs were generally mild or moderate, localized to the site of application, and associated with low discontinuation rates. Medical images are of importance in trials of dermatologic therapies to inform clinical decision-making and enhance patient assessment. Tapinarof cream 1% QD is efficacious and well tolerated in patients with mild to severe plaque psoriasis, with clinically relevant improvements seen early in the course of treatment. Clinicaltrials.gov numbers: NCT03956355, NCT03983980, NCT04053387.